2018
DOI: 10.5194/acp-2018-229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation and growth of atmospheric nanoparticles in the eastern Mediterranean: Results from long-term measurements and process simulations

Abstract: <p><strong>Abstract.</strong> Atmospheric New Particle Formation (NPF) is a common phenomenon all over the world. In this study we present the longest time series of NPF records in the eastern Mediterranean region by analyzing seven years of aerosol number size distribution data obtained with a mobility particle sizer. The measurements were performed at the Finokalia environmental research station on Crete, Greece during the period June 2008–June 2015. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Afterwards, particles continued to grow in size for several hours, exceeding 100nm in diameter at 21:30 LT. Following the methodology of the mode-fitting (Hussein et al, 405 2004;Kulmala et al, 2012) the nucleation mode particles exhibited a growth rate of 3.7 nm h -1 , while the formation rate value of particles in the nucleation mode was 2.0 cm -3 s -1 (Kulmala et al, 2012), which are well in the range of the representative values reported by Kalivitis et al (2018) at Finokalia site.…”
Section: Page 11supporting
confidence: 60%
See 1 more Smart Citation
“…Afterwards, particles continued to grow in size for several hours, exceeding 100nm in diameter at 21:30 LT. Following the methodology of the mode-fitting (Hussein et al, 405 2004;Kulmala et al, 2012) the nucleation mode particles exhibited a growth rate of 3.7 nm h -1 , while the formation rate value of particles in the nucleation mode was 2.0 cm -3 s -1 (Kulmala et al, 2012), which are well in the range of the representative values reported by Kalivitis et al (2018) at Finokalia site.…”
Section: Page 11supporting
confidence: 60%
“…162 NPF episodes were recognized (Kalivitis et al, 2018) and the chemical composition of submicron particulate matter during these episodes was primarily composed of sulfate, 345 contributing on average by 39±8% to the total estimated PM1 mass as derived from the respective bulk PM10 24-h quartz fiber filters, and by 51±12% as derived from the ACSM highresolution measurements, respectively. Moreover, regarding the organic material the contribution was found to be in the order of 38±10% and 44±12%, respectively indicating that…”
Section: Aerosol Chemical Composition and Hygroscopicity During Npf Ementioning
confidence: 99%